Beban Kerja dan Kesejahteraan Guru dalam Perspektif Sosial-Ekonomi - Ardati Ardati; Fania Ramadhani; Ikmawati Ikmawati; Achmad Muhtadin (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2026)
This study aims to analyze the relationship between workload and teacher well-being in a socio-economic context through a literature review approach. Teachers play a crucial role in the success of the education system, but increasing work demands, changes in education policies, and advances in digital learning have increased the complexity of their tasks. Teachers' workload extends beyond the teaching process to include administrative aspects, assessment, student guidance, and other professional responsibilities that can impact their well-being. The methodology used was a literature review, reviewing various academic sources, including journal articles, scientific books, and research reports published between 2021 and 2026. The data were analyzed using content analysis techniques to identify patterns of association between workload and teacher well-being from a social and economic perspective. The study findings indicate that high workload contributes to increased stress, emotional exhaustion, and decreased job satisfaction, particularly when job demands are not supported by adequate resources. Teacher well-being has been shown to be complex, encompassing interrelated economic, psychological, and social factors. Elements such as income, a supportive work environment, and professional recognition are crucial in improving teacher well-being and work motivation. This study emphasizes that managing a proportional workload and improving teacher welfare are strategic steps to support teacher professionalism and the overall quality of education. These findings are expected to serve as a reference for policymakers in formulating strategies to improve teachers' quality of work life.